Comparative genomics of the Leukocyte Receptor Complex in carnivores - Jelinek, April L.; Futas, Jan; Burger, Pamela A.; Horin, Petr (Frontiers in Immunology, 2023)
Background: The mammalian Leukocyte Receptor Complex (LRC) chromosomal region may contain gene families for the killer cell immunoglobulin-like receptor (KIR) and/or leukocyte immunoglobulin-like receptor (LILR) collections as well as various framing genes. This complex region is well described in humans, mice, and some domestic animals. Although single KIR genes are known in some Carnivora, their complements of LILR genes remain largely unknown due to obstacles in the assembly of regions of high homology in short-read based genomes. Methods: As part of the analysis of felid immunogenomes, this study focuses on the search for LRC genes in reference genomes and the annotation of LILR genes in Felidae. Chromosome-level genomes based on single-molecule long-read sequencing were preferentially sought and compared to representatives of the Carnivora. Results: Seven putatively functional LILR genes were found across the Felidae and in the Californian sea lion, four to five genes in Canidae, and four to nine genes in Mustelidae. They form two lineages, as seen in the Bovidae. The ratio of functional genes for activating LILR to inhibitory LILR is slightly in favor of inhibitory genes in the Felidae and the Canidae; the reverse is seen in the Californian sea lion. This ratio is even in all of the Mustelidae except the Eurasian otter, which has a predominance of activating LILR. Various numbers of LILR pseudogenes were identified. Conclusions: The structure of the LRC is rather conservative in felids and the other Carnivora studied. The LILR sub-region is conserved within the Felidae and has slight differences in the Canidae, but it has taken various evolutionary paths in the Mustelidae. Overall, the process of pseudogenization of LILR genes seems to be more frequent for activating receptors. Phylogenetic analysis found no direct orthologues across the Carnivora which corroborate the rapid evolution of LILRs seen in mammals.